2009
DOI: 10.1111/j.1463-1318.2009.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal anatomical disruption in stoma formation: the lateral rectus abdominis positioned stoma (LRAPS)

Abstract: LRAPS reduces the incidence of early stomal herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…The LRAPS was first described by Stephenson; this stoma trephine preserves the width of the rectus muscle and minimizes disruption of the layers of the abdominal wall. No PSH was demonstrated in a small series of 24 patients with a short‐term median follow‐up of 13 months (range 7–18 months) . A feasibility RCT of 56 patients in the PATRASTOM trial found no difference in PSHs between the transrectal and LRAPS approach.…”
Section: Resultsmentioning
confidence: 97%
“…The LRAPS was first described by Stephenson; this stoma trephine preserves the width of the rectus muscle and minimizes disruption of the layers of the abdominal wall. No PSH was demonstrated in a small series of 24 patients with a short‐term median follow‐up of 13 months (range 7–18 months) . A feasibility RCT of 56 patients in the PATRASTOM trial found no difference in PSHs between the transrectal and LRAPS approach.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed they state that positioning of the ileostomy trephine above the arcuate line was ‘ not always practicable ’. This, however, is an essential step in LRAPS formation and the site should almost be at the level of the umbilicus where the posterior rectus sheath is always present. Indeed, in over 20 years of raising stomas (LRAPS type from July 2007) neither my stomatherapists nor I have had complaints regarding the position (height) of a stoma, especially when patients know it is temporary.…”
mentioning
confidence: 99%
“…Parastomal herniation is an oft encountered problem when the trephine is raised through the belly of the rectus muscle, as is traditionally done and illustrated in the video. With this in mind, the lateral rectus abdominis positioned stoma (or LRAPS) technique to stoma formation was described, with the aim of minimizing abdominal wall disruption and subsequent hernia formation . Briefly, dissection employs horizontal (rather than cruciate) incisions in the sheaths above the arcuate line of Douglas, with the rectus muscle swept medially to accommodate the trephine.…”
mentioning
confidence: 99%